Let's get it on: Addressing sex and intimacy in older cancer survivors. Issue 2 (March 2021) - Arthur, Elizabeth K.; Worly, Brett; Carpenter, Kristen M.; Postl, Claire; Rosko, Ashley E.; Krok-Schoen, Jessica L.; Quick, Allison M.; Jenkins, Lawrence C.
Highlights: Vaginal moisturizers and lubricants are low-risk treatments for dryness and pain. PDE5i medications are helpful for erectile dysfunction in older men with cancer. Sex therapy addresses distress from decreased libido, arousal/orgasm, or pain. Healthy lifestyle, stress management, and counseling help optimize sexual health.